Assessment of the contribution of community share ownership schemes or trusts on the Zimbabwean economy: the case of Mhondoro Ngezi CSOS - Moses, Blessing (Midlands State University, 2017)
The article primarily analyses the effectiveness of the economic empowerment strategies targeted at the community of Mhondoro Ngezi Rural district. Despite abundant mineral resources, the indigenous communities living close to the mines have been deprived of the right to directly or indirectly benefit from the mineral resources. The study utilised a descriptive survey to collect data. The article gives a strong indication of how communities of Mhondoro Ngezi Rural district can utilise the Indigenisation and Economic Empowerment Act and the Statutory Instrument 21 of 2010 (Community Share Ownership Trust) to empower themselves. The findings of the study indicated that the Indigenisation and Economic Empowerment Act and Statutory Instrument for Community Share Ownership Trust were the pro poor mining policies that ensured the harnessing of mineral resources for the empowerment of local indigenous communities. It was also found out that the Indigenisation and Economic Empowerment Act needed to be harmonised with the Rural District Councils’ Act, the Mines and Minerals Act, and the Communal Areas Management Act. The article concluded that the development of infrastructure and provision of public utilities such as electricity, water, establishing micro-credit to small and medium enterprises and implementing broad-based indigenisation policies were some of the strategies of improving rural livelihoods and stimulating entrepreneurship in communities living close to mines. The article recommends that the harmonisation of these acts will ensure that empowerment is integrated in all legislation focused on rural development and promote sustainable ways of utilising the Community Share Ownership Trust